The effect of educational intervention on preventive behaviors against cutaneous leishmaniasis in employees of Shiraz special economic zone subsidiary companies - Afsaneh Ghasemi; Fatemeh Mohammadkhah; Hasan Bahja; Amirhossein Kamyab; Ali Khani Jeihooni (BMC Public Health)
Abstract Background Leishmaniasis is a major public health and veterinary challenge in Mediterranean countries. Preventing infection is the most critical measure, and educational interventions can be utilized to modify preventive behaviors against cutaneous leishmaniasis (CL). Therefore, this study aimed to evaluate the effect of an educational intervention on preventive behaviors against CL in employees of Shiraz Special Economic Zone subsidiary companies. Methods This experimental study was conducted on 280 employees of Shiraz Special Economic Zone subsidiary companies, Iran, during 2023–2024 (140 participants in the control group and 140 in the intervention group). Data were collected using a questionnaire that included demographic information, awareness assessment, constructs of the Health Belief Model (HBM), and preventive behaviors against CL. The questionnaire was completed by both groups before and three months after the intervention. The intervention group attended eight educational sessions, held weekly, lasting 50–60 min each. Results The mean age of the intervention group was 40.38 ± 6.78 years, and the control group was 38.92 ± 7.16 years. Results showed a significant change in the mean scores of all Health Belief Model constructs in the intervention group after the educational sessions (P < 0.05). Additionally, significant changes were observed in the mean scores of perceived susceptibility (P < 0.001), perceived barriers (P < 0.001), self-efficacy (P < 0.001), and cues to action (P < 0.001) between the intervention and control groups after the intervention (P < 0.05). Conclusion The results demonstrated that applying the Health Belief Model was beneficial and effective in enhancing preventive behaviors against CL. This approach can be practical in promoting the health of individuals at risk.